Public health surveillance for behavioral risk factors in a changing environment: recommendations for the Behavioral Risk Factor Surveillance Team. - Mokdad AH; Stroup DF; Giles WH (MMWR: Morbidity & Mortality Weekly Report)
The Behavioral Risk Factor Surveillance System (BRFSS) is a state-based system of health surveys. Information regarding health risk behaviors, clinical preventive health practices, and health-care access, primarily related to chronic disease and injury, is obtained from a representative sample of adults in each state. Approximately 200,000 adult interviews are completed each year in all 50 states, the District of Columbia, Puerto Rico, the Virgin Islands, and Guam. The challenge for BRFSS is how to effectively manage an increasingly complex surveillance system that serves the needs of numerous programs while facing changing telecommunication technology and the greater demand for more local-level data. To determine options and recommendations for how best to meet BRFSS future challenges, CDC's Behavioral Surveillance Branch conducted a 2-day strategy workshop, attended by survey-research specialists. The workshop featured presentations on the current system; emerging technologic challenges; telephone-surveying techniques; program perspectives of CDC, partner organizations, and states; and recommendations for change. This report summarizes the recommendations resulting from that workshop.